A kaolinite-based design of kaolin/TiO2–PAM composite flocculant and the application of the oil sand tailings flocculant. Issue 4 (1st March 2021) - Ji, Cheng; Wei, Xinfang; Wang, Haiwang; Chao, Li; Li, Jinlong; Qi, Xiwei
Abstract: We prepared an efficient kaolin–TiO2 –polyacrylamide (PAM) organic–inorganic composite flocculant; the synthesis process is simple and suitable for mass industrial production. First, the surface of kaolin was modified with titanium dioxide, and then the acrylamide monomer was initiated on the surface by a surface-initiated polymerization method; thus, the PAM polymer was successfully grown on the surface of kaolin, thereby effectively improving the water-reducing efficiency. Utilizing good adsorption properties for impurities of kaolin itself and via regulation of the degree of polymerization of the PAM polymer, the cost could be effectively reduced and the water-reducing efficiency could be improved. Further, the microstructure and morphology were observed by scanning electron microscope and transmission electron microscopy, and elemental analysis was carried out by X-ray photoelectron spectroscopy. The results showed that nano-titanium dioxide was successfully loaded onto the surface of kaolin and the surface of the composite particles was successfully coated with PAM. The functional groups before and after the synthesis of the material were characterized. Further confirmed that the surface of the composite ion was successfully coated with PAM. In addition, the thermodynamic stability of the prepared material was analyzed by thermogravimetry; the average PAM content was 53.7 wt%. Furthermore, from the flocculation experiment (tested with simulated oil sand tailings), it was found that the water-reducing rate of the kaolin–TiO2 –PAM organic–inorganic flocculant toward the flocculation of oil sand tailings exceeded 85%, and the transmittance increase exceeded 94%. Finally, the flocculation behavior and flocculation mechanism of the kaolin–TiO2 –PAM composites under different flocculant dosages and pH conditions were carefully studied. Abstract :